Reduction of H3K27cr Modification During DNA Damage in Colon Cancer - Liao, Meijian; Chu, Weiwei; Sun, Xiaolin; Zheng, Wendan; Gao, Shoucui; Li, Danhua; Pei, Dongsheng (Frontiers in Oncology, 2022)
DNA damage plays an essential role in the initiation and development of colon cancer. Histone crotonylation is a newly discovered post-translational modification that is thought to promote gene expression. Whether histone crotonylation plays a role in DNA damage of cancer remains unknown, as does the putative underlying molecular mechanism. This study aimed to investigate the relationship between histone crotonylation and DNA damage of colon cancer using multiple bioinformatics analysis and western blotting. We discovered that genes with promoter occupied by histone crotonylation were associated with the activity of DNA damage in colon cancer patients. Additionally, we uncovered that the level of crotonylation on Lys27 of histone H3 (H3K27cr) decreased during camptothecin (CPT) and etoposide (VP16) treatment. Interestingly, sirtuin 6 (SIRT6) was found to regulate the cellular level of H3K27cr. Taken together, our study provided a new perspective about histone crotonylation and DNA damage in colon cancer.